2010
DOI: 10.1002/jcla.20379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the poly(ADP‐ribose) polymerase‐1 gene variants in Alzheimer's disease

Abstract: Amyloid peptide is thought to play a critical role in neuronal death in Alzheimer's disease (AD), most likely through oxidative stress. Free radical-related injury leads to DNA breaks, which subsequently activates the repair enzyme poly(ADP-ribose) polymerase-1 (PARP-1). In this study, the relationship between genetic variants situated at the PARP-1 gene and AD development was investigated. We performed a case and control study from a Taiwanese population enrolled 120 AD patients and 111 healthy controls by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Postmortem studies observed decreases in DNA glycosylase activity: UDG (uracil DNA glycosylase) and hOGG1, DNA polymerase β, as well as the overall BER in brain cells of AD patients compared to brain cells of patients with mild cognitive impairment, suggesting a relationship between BER performance and degree of neurodegeneration in these cells [11]. Polymorphisms of the BER gene PARP may also play a role in the pathogenesis of AD [12]. In the case of Parkinson's disease (PD), which is another neurodegenerative disorder, there is a positive association of apurinic/apirimidinic site endonuclease ( APE1; g.20456995T>G), X-ray repair cross-complementing protein 1 encoding XRCC1 protein (c.1196A>G), and XRCC3 (g.103699416G>A) DNA repair gene polymorphisms and increased PD risk [13].…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem studies observed decreases in DNA glycosylase activity: UDG (uracil DNA glycosylase) and hOGG1, DNA polymerase β, as well as the overall BER in brain cells of AD patients compared to brain cells of patients with mild cognitive impairment, suggesting a relationship between BER performance and degree of neurodegeneration in these cells [11]. Polymorphisms of the BER gene PARP may also play a role in the pathogenesis of AD [12]. In the case of Parkinson's disease (PD), which is another neurodegenerative disorder, there is a positive association of apurinic/apirimidinic site endonuclease ( APE1; g.20456995T>G), X-ray repair cross-complementing protein 1 encoding XRCC1 protein (c.1196A>G), and XRCC3 (g.103699416G>A) DNA repair gene polymorphisms and increased PD risk [13].…”
Section: Introductionmentioning
confidence: 99%
“…Again, none of the polymorphisms resulted independently associated with increased AD risk (Table 2). However, authors found that the distributions of haplotype 3-TT and haplotype 4-CC were significantly associated with an increased risk of AD, whereas the haplotype 1-TC showed a protective effect, with OR of 12.2 and 0.52, respectively (Liu et al, 2010). Overall, both studies support the hypothesis that PARP1 haplotypes might affect AD risk.…”
Section: Polymorphisms Of Dna Repair Genes and Alzheimer's Diseasementioning
confidence: 66%
“…Particularly, haplotypes 2-1 and 1-2 were significantly overrepresented in AD individuals and associated with an increased risk for the disease with an adjusted OR of 1.42 and 5.38, respectively . More recently two PARP-1 exonic polymorphisms, 414C>T (rs1805404) and 2456T>C (rs1136410), have been evaluated in 120 Chinese AD patients and 111 matched controls (Liu et al, 2010). Again, none of the polymorphisms resulted independently associated with increased AD risk (Table 2).…”
Section: Polymorphisms Of Dna Repair Genes and Alzheimer's Diseasementioning
confidence: 99%
“…Although many studies have searched for the association between PARP-1 polymorphisms and the risk of malignancy, the results are inconsistent in different organs and in different ethnic groups. Few studies have reported positive associations between the SNP's rs1805404 and rs1805414 at position 81 and 284, have been reported to be significantly associated with an increased risk of Alzheimer's disease (Liu et al, 2010), Glioblastoma (Keller et al, 2011), protectively associated with Colorectal cancer (Berndt et al, 2007;Ogino et al, 2010). rs1805404 reported be strongly associated with Tourette syndrome risk (Wu et al, 2013).…”
Section: The C Allele Of a Synonymous Snp (Rs1805414 Ala284ala) In Pmentioning
confidence: 99%